2013
DOI: 10.1007/s12035-013-8561-0
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Susceptibility SNPs for Ischemic Stroke Using Exome Sequencing in Chinese Han Population

Abstract: Genome-wide association studies (GWAS) of ischemic stroke (IS) have been performed on several cohorts of Caucasian or African population and Japanese, resulting in somewhat inconsistent conclusion. We aimed to identify susceptibility loci for IS by exome sequencing in a Chinese Han population. Exome sequencing was used to screen susceptibility loci among 100 cases and 100 matched controls. Significant SNPs from the first stage were verified in up to 3,554 participants from three hospital-based case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The motive that initiates the conduction of this study was the association that we found between SYK gene polymorphism and the risk of IS, which was identified by exome sequencing in one of our previous studies, while not yet published. In recent years, studies about the role of SYK gene in stroke have attracted great research interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The motive that initiates the conduction of this study was the association that we found between SYK gene polymorphism and the risk of IS, which was identified by exome sequencing in one of our previous studies, while not yet published. In recent years, studies about the role of SYK gene in stroke have attracted great research interest.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were recruited from Shenzhen People's Hospital between June 2014 and December 2016. All cases were inpatients diagnosed with IS for the first time and were recruited based on the appearance of a new and abrupt focal neurological deficit, with neurological symptoms and signs persisting for more than 24 hours, as described previously . IS was confirmed by positive findings on head CT or MRI according to the International Classification of Disease (9th Revision, codes 430 to 438).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,31,32 This approach has been previously reported in other two studies on stroke patients. 33,34 The first one by Zhang et al 2014 applied the exome sequencing analysis to a population of 100 Chinese stroke patients and controls, reporting an association with 2 genes with uncertain significance. Moreover, as reported by the same author, this study is biased by the poor population characterization and by the possible founder effect because of the recruitment area (Beijing and Shenzhen).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded Matsushita et al (2010) 7 and Zhang et al (2012) 8 which were large candidate gene studies, Zhang et al (2014) 9 which was a whole exome sequencing (WES) study, Cole et al (2012) 10 and Zhou et al ( 2014) 11 which were small WES studies examining 10 and 9 subjects respectively; Opherk et al (2014) 12 which described white mater hyperintensity (WMH) volume in cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL); Keene et al (2014) 13 which described SNPs significantly associated with Vitamins B6 and B12 in stroke patients (not as a risk of stroke); and Traylor et al (2017) 14 which was not a GWAS study, but an heritability study which also applied genetic risk score.…”
Section: 0 Methodsmentioning
confidence: 99%